Needs Analysis in the Development of Basic Physics Practical E-Module Based on Interactive Flipbook with STEM Approach - Marisda, Dewi Hikmah; Nurlina, Nurlina; Nurazmi, Nurazmi; Handayani, Yusri; Hasin, Ardiansah; Hamzah, Hardi (JIPF (Jurnal Ilmu Pendidikan Fisika), 2024)
The low interest of students in reading the practicum guide is the focus of the problem in this study. This study is a survey study which is part of development research. This study aims to describe the define stage at the needs analysis stage (initial-final analysis and student analysis), identification of Basic Physics material, and identification of resources. The research data were analyzed descriptively. The study results indicate that the curriculum applied to the Physics Education Study Program at one of the Muhammadiyah Universities in Makassar is the MBKM-oriented KKNI curriculum. The initial-final analysis found that the Basic Physics practicum module was still conventional and in printed form, manually distributed to students. Student analysis found that students' learning styles were visual. The specification-identification of Basic Physics material found that the essential material for Basic Physics practicum consisted of five experimental units that would be developed. Information was obtained from the identification of resources that all students had smartphones that could access the practicum e-module. Therefore, the practicum e-module that will be developed will direct students to visual activities like user-friendly flipbooks and easily accessible via students' smartphones.